Lingkungan Kerja Auditor Dan Pilihan Karirnya Sebagai Auditor : Perspektif Mahasiswa Akuntansi: Auditor's Work Environment and Career Choices as an Auditor: Accounting Student Perspectives - Biduri, Sarwendah (Journal of Accounting Science, 2017)
This study attempts to try and get empirical evidence perceptions regular students and non regular accounting prodi school of economics and business muhammadiyah university sidoarjo about auditor work environment on their carrier choice as auditors .This research kind of quantitative research The data that had been collected were obtained through distributing questionnaires to 70 redpondents who were student active first half of 5 and 7 gasal 2016-2017 force. This study used analytics normality and the test t independent sampel-test with on the spss version 19 for windows. The result of the research there is a difference of the perceptions student non regular or regular accounting of auditors about the auditor work environment at the economic and business muhammadiyah university sidoarjo with differences a perception of his career as auditors choice between student regular or regular non of accounting in school of economics and business Muhammadiyah University Sidoarjo